Analysis of factors influencing commercial off take rate and marketing of small ruminants kept under different production systems in Egypt - Metawi H.R.M. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
This study was conducted to assess the determinants of sheep and goats market supply in two agroecological regions located in the north coastal zone of Egypt: (i) the rain fed region in the west, where pastoralists and agro-pastoralists are the dominant economic activity (ii) the irrigated region in the east, where the mixed crop-livestock production system is prevailing. A structure questionnaire was used to collect information from 155 small ruminant owners based on single-visit-interviews. Analysis of data showed that flock differed in size and composition among different agro-ecological regions. In general, very low net commercial off –take rate is observed for both sheep and goats for farmers in the east and pastoralist regions. In most instances, households sold animals of varying sex, age and weight to cover immediate cash needs. Household non farm income and sizes of flock, family and farm had significant impact on their market participation. Specific recommendations are made to obtain sustained high off take rates and commercial supply of quality live animals in the market.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)